Psychosocial resilience surrounding age-typical losses among older adults in Sweden: group-based trajectories over a 25-year-period - Agahi, Neda; Augustsson, Erika; McGarrigle, Christine; Rostgaard, Tine; Fritzell, Johan (Frontiers in Public Health, 2024)
Introduction Resilience is an important but often neglected aspect of healthy or successful aging. This study used a new approach for modelling psychosocial resilience to investigate responses when faced with age-typical losses. Rather than viewing resilience as a trait, we modelled trajectories of life satisfaction when faced with partner or functional loss in later life to identify resilient trajectories. Then, we examined characteristics associated with belonging to resilient trajectories. Method We analyzed longitudinal data from the individually linked Swedish LNU and SWEOLD surveys collected repeatedly between 1991 and 2021 (N = 450). A group-based trajectory modelling technique was used to obtain trajectories of life satisfaction over time, centered around the first identified loss. Identified losses (widowhood, loss of mobility and loss of vision), occurred between ages 60 and 98. Results Four trajectories of life satisfaction surrounding loss were identified, labelled Declining (46%), Non-recovering (24%), Recovering (16%), and Bouncing back (14%). The latter two were categorized as resilient. Individuals in resilient trajectories were more likely to be younger, engaged more with their friends after the loss, reported fewer mental health problems both before and after the loss, and had a higher sense of control before the loss. Discussion Several interesting patterns of long-term change in life satisfaction were found in response to loss. Contrasting earlier findings, only about one-third of the sample was categorized as resilient. The two resilient trajectories were characterized by either quick adaptation or a slower adaptive process. Increasing or maintaining social networks, particularly friendships, after an age-typical loss may promote resilience.